OntOraculum: A Semantic Ontology for Monitoring and Optimizing Performance Metrics in Smart Environments - Darlan Noetzold; Valderi Leithardt; Jorge Luis Victória Barbosa (SSRN Electronic Journal, 2025)
This study presents OntOraculum, an ontology designed to organize and analyze performance metrics in smart environments. It categorizes metrics into Hardware, Network, Software, Energy, and SecurityAndReliability domains, defining properties such as dependencies, impacts, and trends to support predictive analysis and dynamic adjustments. Using Protégé for modeling, SWRL rules for inferences, and SPARQL queries for validation, this ontology addresses questions related to network latency, energy efficiency, security, quality of service, and anomaly detection. By unifying performance metrics across diverse domains, OntOraculum enables comprehensive analysis of dependencies and interactions among metrics. The results demonstrate its practical applicability for monitoring, optimizing, and adapting systems in distributed environments. Keywords: Ontology, Performance Metrics, energy efficiency, Smart Environment